Nonverbal elements of leadership behaviour - Birgit Schyns; Gisela Mohr (Zeitschrift für Personalforschung (ZfP), 2004)
In this theoretical paper, we investigate the importance of nonverbal behaviour in the context of leadership. Research on the decoding of social interactions has shown that the quality or type of relationship as well as relationally relevant emotional states are transmitted nonverbally. With this in mind, we review the existing literature on nonverbal leadership behaviour, such as research on Pygmalion leadership or political leadership. The nonverbal behaviours examined in these research areas show remarkable consistency and we therefore conclude that it is possible to deduce about effective nonverbal leadership behaviours. Still, many points remain open for further research and discussion. For example, no information is available concerning nonverbal behaviour in negative feedback processes. We conclude by outlining fruitful research directions in the area of nonverbal behaviour in leadership.
Keywords: 650; Leadership; Interaction; Nonverbal Behaviour